2020
DOI: 10.1016/j.actamat.2020.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities in the periodic arrangement of elastically interacting precipitates in nickel-base superalloys

Abstract: Nickel-base superalloys display cuboidal precipitates aligned along the cubic directions, which are the elastic soft directions. At high precipitate volume fraction, the microstructure is often described as a regular array of precipitates organized on a simple cubic macro-lattice. In the present work, we use a stability analysis and 3D phase field simulations to show that such a regular array is in fact unstable whatever the volume fraction of precipitates. The two main instability modes are the longitudinal [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The phase-field method has been used extensively to simulate precipitation in a wide range of metallic alloys, such as Ni [42,, Ti [68][69][70][71][72][73][74][75], Al [76][77][78][79][80][81][82][83][84][85], and Mg [86][87][88][89][90][91][92][93][94][95][96] alloys. Research studies have covered a series of aspects related to the growth and coarsening of precipitates, such as the shape and distribution of precipitates [47,80,88], the interactions between precipitations and external stress fields, such as the stress fields caused by other precipitates [89,94] or lattice defects [88,92], and the directional coarsening (rafting) and stability of cuboidal matrix/precipitate microstructures in superalloys [55][56][57][58][59][60][61][62]…”
Section: Precipitationmentioning
confidence: 99%
“…The phase-field method has been used extensively to simulate precipitation in a wide range of metallic alloys, such as Ni [42,, Ti [68][69][70][71][72][73][74][75], Al [76][77][78][79][80][81][82][83][84][85], and Mg [86][87][88][89][90][91][92][93][94][95][96] alloys. Research studies have covered a series of aspects related to the growth and coarsening of precipitates, such as the shape and distribution of precipitates [47,80,88], the interactions between precipitations and external stress fields, such as the stress fields caused by other precipitates [89,94] or lattice defects [88,92], and the directional coarsening (rafting) and stability of cuboidal matrix/precipitate microstructures in superalloys [55][56][57][58][59][60][61][62]…”
Section: Precipitationmentioning
confidence: 99%
“…close and the analytic model shows the same plateau for large misfit ratios. Figure 5b) shows the orientation dependent elastic relaxation function B ( n) that quantifies soft and hard crystallographic directions independent of the precipitate shape [15,46,81]. It is defined as…”
Section: Variation Of Anisotropic Misfit and Elastic Constantsmentioning
confidence: 99%
“…It is limited by being only a realistic description of a uniform single-variant microstructure that does not take into account the kinetics of precipitate growth that might have strong influence on the shapes of experimentally observed precipitates [91]. It was also found that a periodic arrangement of precipitates must not always be a stable configuration [46]. CONCLUSION We evaluate influencing factors on equilibrium shapes of γ precipitates in Ni-based superalloys considering one S l a m a e t a l .…”
Section: Energy Density Of the γ/γ Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…The elastic effect observed in the experiments is well studied through PF models for binary and ternary systems [36][37][38][39][40][41]. Degeiter, et al [42] studied the microstructure formation in Nickel-based alloys based on PF simulations, and revealed that the periodic arrangement of cuboidal precipitates is unstable, which may lead to the formation of defects related to experimental observations. Hong et al [43,44], investigated the precipitation process of β phase in Mg based binary and ternary alloys, results show that the growth behavior of the precipitates determined by the elastic strain energy minimization.…”
Section: Introductionmentioning
confidence: 99%